Rehabilitation of an Upper Extremity Weight-Bearing Athlete with an Ulnar Collateral Ligament Injury: A Case Report - Annemieke D. Corbitt; William D. Bandy (International Journal of Sports Physical Therapy)
# Background and Purpose